Leachate treatment using limestone and subsurface flow constructed wetland - Muhammad Azizuddin , Mohd Haris (2012)
Leachate is a complex and highly polluted wastewater which produced from solid waste in landfill. Leachate has high content of heavy metals, chlorides, organic nitrogen, phosphate, sulphate and high in organic matters and inorganic ion concentrations. Due to the concentration of leachate that highly polluted, the treatment process is very complicated, expensive and generally requires multiple processes. Therefore, the purpose of this study was to assess the impact of the combination of limestone and subsurface flow constructed wetland in treating a landfill leachate. Size of limestone that has been used in the limestone filter was 5mm to 12mm while type of plant used in the subsurface flow constructed wetland was common cattail (Typha Latjfolia). Sample of raw leachate was collected from Jerangau-Jabor Landfill, Kuantan. There are several parameters considered in this study which are BOD5 , COD, TSS, ammoniacal nitrogen and heavy metals (Fe, Pb, Cu, Mn, Zn, Cr). In addition, the treatment processes conducted in two modes which are hourly treatment mode and daily treatment mode. Based on the analysis, the combination of limestone and subsurface flow constructed wetland are effective in treating leachate. The percentage removal; BOD 5 56.40/0, COD 97.7%, TSS 99.00/0, ammoniacal nitrogen 99.2% while for Fe, Pb, Cu, Mn, Zn and Cr is 100%. Thus, these show that the treatment system is very efficient in removing contaminants in the landfill leachate.